THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE ACCOUNTING PROFESSION IN THE ERA OF INDUSTRY 4.0 AND SOCIETY 5.0 - Evi Martaseli; Maragita Maragita (JASS (Journal of Accounting for Sustainable Society), 2023)
The accounting profession has changed as a result of advances in information technology in artificial intelligence. The accounting profession around the world recognizes the impact of the latest technological advances in Big Data, Machine Learning and Artificial Intelligence in the Industry 4.0 and Society 5.0 era. The aim of this research is to find out how the accounting profession has changed over time in response to recent advances in technology and how these changes may affect the future of the profession. The difficulties and opportunities presented by AI in professional accounting and the accounting education process. This study uses a qualitative method which includes literature review and secondary data. This research provides an overview of how the impact of AI and what accountants have to do in order to respond to technological developments and is then discussed by the accounting profession.